New “Smart” Systems for Atmospheric Aerosol and Reactive Gas Sampling in Ambient Air - Paolo Cristofanelli; Maurizio Busetto; Enrico Ronchi; Paolo Miatto; Angela Marinoni; Francescopiero Calzolari; Paolo Bonasoni; Luca A. Tagliafico (Sensors, 2018)
Nowadays a recognized need for accurate observations of atmospheric aerosols (AEs) and reactive gases (RGs) exists in the framework of regional, national and global near-surface networks based on permanent or mobile measurement stations. In this context, a paramount and not-trivial issue is related to the correct execution of continuous sampling of ambient air and its subsequent distribution to measurement analyzers hosted inside the stations. Sampling artifacts must be minimized for obtaining reliable pictures of ambient air composition. To respond to this need, a suite of novel “smart„ and relatively low-cost systems for the continuous sampling of ambient air was developed in the framework of the 2012⁻2015 I-AMICA Project. These systems were designed to execute AE and RG measurements according with WMO/GAW and ACTRIS recommendations and standard operation procedures. A particular attention was dedicated to the stabilization and control of the sampling flow rates and temperatures. The analysis of one full year of operations at the WMO/GAW regional station of Capo Granitola (GAW ID: CGR, Italy), allowed to conclude that these systems are effective in meeting the technical requirements for correct execution of AE and RG measurements.